What is the risk of European sovereign debt defaults? Fiscal space, CDS spreads and market pricing of ristk - Joshua Aizenman; Michael Hutchison; Yothin Jinjarak (University of California, Santa Cruz Institute for International Economics (SCIIE), 2011)
We estimate the pricing of sovereign risk for sixty countries based on fiscal space (debt/tax; deficits/tax) and other economic fundamentals over 2005-10. We measure how accurately the model predicts sovereign credit default swap (CDS) spreads, focusing in particular on the five countries in the South-West Eurozone Periphery (Greece, Ireland, Italy, Portugal, and Spain). Dynamic panel estimates of the model suggest that fiscal space and other macroeconomic factors are statistically significant and economically important determinants of market-based sovereign risk. Although the explanatory power of fiscal space measures drop during the crisis, the TED spread, trade openness, external debt and inflation play a larger role. As expectations of market volatility jumped during the crisis, the weakly concavity of creditors' payoff probably accounts for the emergence of TED spread as a key pricing factor. However, risk-pricing of the South-West Eurozone Periphery countries is not predicted accurately by the model either in-sample or out-of-sample: unpredicted high spreads are evident during global crisis period, especially in 2010 when the sovereign debt crisis swept over the periphery area. We match the periphery group with five middle income countries outside Europe that were closest in terms of fiscal space during the European fiscal crisis. We find that Eurozone periphery default risk is priced much higher than the matched countries in 2010, even allowing for differences in fundamentals. One interpretation is that the market has mispriced risk in the Eurozone periphery. An alternative interpretation is that the market is pricing not on current fundamentals but future fundamentals, expecting the periphery fiscal space to deteriorate markedly and posing a high risk of debt restructuring. Adjustment challenges of the Eurozone periphery may be perceived as economically and politically more difficult than the matched group of middle income countries because of exchange rate and monetary constraints.
Keywords: E43; F30; G01; H63; 330; CDS spreads; sovereign risk; fiscal space; default risk; Eurozone; Finanzmarktkrise; Öffentliche Schulden; Insolvenz; Risiko; Welt